Efficacy and safety of infliximab in very early onset inflammatory bowel disease: a national comparative retrospective study. Issue 6 (1st July 2019) - Bramuzzo, Matteo; Arrigo, Serena; Romano, Claudio; Filardi, Maria Chiara; Lionetti, Paolo; Agrusti, Anna; Dipasquale, Valeria; Paci, Monica; Zuin, Giovanna; Aloi, Marina; Strisciuglio, Caterina; Miele, Erasmo; et al.
Abstract : Background: Very few data regarding the use of infliximab in children with very early‐onset inflammatory bowel disease (VEO‐IBD) have been reported. Objective: We aimed to assess the efficacy and the safety of infliximab in children with VEO‐IBD compared with older children. Methods: Children treated with infliximab were identified within the Italian IBD registry. The primary outcome was the rate of clinical remission at weeks 14 and 54. Secondary outcomes included the proportion of partial clinical response, treatment duration, and incidence of adverse events. Results: Forty‐two children with VEO‐IBD were compared with 130 children with IBD. Despite significantly higher infliximab withdrawals in VEO‐IBD patients during induction (42.9% vs 7.7% p < 0.01), remission rates at week 14 were similar (28.6% vs 43.8%, p = 0.10). At week 54 fewer VEO‐IBD children were in remission (15.8% vs 54.3%, p < 0.01). The treatment duration was shorter in VEO‐IBD (median 12.0 vs 18.4 months, p < 0.01). During the induction phase, adverse events were more common in the VEO‐IBD group ( p < 0.01). Conclusion: Compared with older children, VEO‐IBD patients have higher rates of infliximab failures, lower remission rates at one year, and more often experience adverse events during induction.